Fahr's disease presenting with pure dementia: A case report and literature review - Jamir Pitton Rissardo; Ana Letícia Fornari Caprara; Juliana Oliveira Freitas Silveira (Apollo Medicine)
Fahr's disease (FD) is a rare inherited or sporadic disorder characterized by symmetrical calcium deposits in the basal ganglia and dentate nuclei with the absence of biochemical abnormalities. Clinical manifestations can start at different ages with a variety of presentations. We report a case of a 68-year-old male who presented to our service with clinical signs and symptoms of pure and progressive dementia. Afterward, he developed mood changes, and finally, movement disorders, probably due to a sporadic form of FD. Noncontrast cranial computed tomography scan demonstrated scattered brain parenchyma, bilateral calcifications in the basal ganglia, and dentate nuclei. Standard blood tests were within the normal limits. In this way, FD can present with pure dementia at onset, reflecting a wide range of neurological manifestations. The diagnosis is challenging, and we proposed an acronym to facilitate the learning of the diagnostic criteria.